Deformation-enhanced recrystallization of titanite drives decoupling between U-Pb and trace elements - Gordon, S.M.; Kirkland, Chris; Reddy, Steven; Blatchford, H.J.; Whitney, D.L.; Teyssier, C.; Evans, Noreen; McDonald, B.J. (ELSEVIER, 2021)
Titanite is a common accessory mineral that is useful in determining both age (U-Pb isotopes) and pressure-temperature (P–T) conditions (trace-element composition: Zr, rare earth elements (REE)). However, titanite has a propensity to recrystallize during metamorphism, fluid flow, and deformation, which can result in modifications to its isotopic and trace-element compositions. This modification has implications for the interpretation of titanite dates and the evaluation of pressure–temperature–time paths. The impact of deformation and recrystallization on trace-element mobility in titanite is investigated through microstructural and compositional mapping of titanite crystals from a sheared orthogneiss within an ultrahigh-pressure domain of the Western Gneiss Region (WGR), Norway. Results show that optically coherent titanite single crystals deformed in the dislocation creep regime and recrystallized by the process of grain-boundary migration, forming aggregates of titanite grains. Some of the aggregate grains record Caledonian-exhumation dates, whereas others have an inherited isotopic composition. Individual grains within the aggregate, regardless of their U-Pb isotopic composition, contain patchy zoning that formed during syn- to post-recrystallization fluid alteration and that is characterized by generally decreasing Ca and Ti and increasing Al and Fe from cores to rims. However, Zr and Sr concentrations are broadly zoned with respect to the long axis of the host crystal, without regard for the aggregate grain boundaries. REE do not show any obvious correlation with microstructure or age. These results indicate that many trace elements in titanite are unaffected by multi-stage, deformation-driven recrystallization; in contrast, Pb is variably mobile in these deformed titanite crystals. The combination of microstructural and high-spatial resolution geochemical and isotopic data reveals the potential extent of decoupling between the U-Pb isotopic system and the behavior of trace elements as pressure–temperature conditions change through time.